Efficiency of Laser Coagulation of the Retina in Patients with Complicated Myopia - S. A., Boboev (American Journal of Biology and Natural Sciences, 2025)
Complicated myopia, also referred to as pathological or degenerative myopia, is characterized by progressive axial elongation of the eyeball, leading to structural and functional changes in the posterior segment of the eye. These alterations include chorioretinal atrophy, posterior staphyloma, and peripheral retinal degenerations that significantly increase the risk of retinal detachment and irreversible vision loss. The aim of this study is to evaluate the clinical effectiveness of laser coagulation therapy in patients diagnosed with complicated myopia in terms of preventing retinal detachment, halting degenerative changes, and preserving visual function. This prospective clinical study involved 60 patients (120 eyes) aged 18–55 years with high-grade myopia and peripheral retinal degenerations. All patients underwent argon laser photocoagulation targeted at areas of lattice degeneration, thinning, or breaks in the peripheral retina. Follow-up assessments were conducted at intervals of 1, 3, 6, and 12 months to monitor anatomical stability and visual acuity. The results indicated that 85% of treated eyes demonstrated stabilized retinal conditions with no new peripheral breaks, and 70% showed stable or improved visual acuity. These findings confirm that laser photocoagulation is a reliable and effective prophylactic intervention for the prevention of sight-threatening complications in complicated myopia.